Determinants of Audit Quality in the Public Sector - Sangkot Khadijah; Yusnita Nasution; Dewi Husnainy; Gina Ariesta Gobel; Dito Aditia Darma Nasution (International Journal of Management, Economic and Accounting, 2025)
Audit quality plays a vital role in strengthening accountability and improving financial governance in the public sector. High-quality audits are essential to ensure transparency, reliability of financial information, and public trust in government institutions. However, studies examining audit quality in the public sector, particularly in Indonesia, remain relatively limited compared to the extensive body of research focusing on the private sector. This study aims to systematically review and synthesize the existing literature related to the determinants of audit quality in the public sector. The research method employed is a literature review of national and international scholarly articles published between 2017 and 2021. The review results indicate that public sector audit quality is influenced by several key factors, including auditor competence and independence, professional skepticism, compliance with auditing standards and professional ethics, auditor motivation, and time budget pressure. In addition, the work environment and limitations in resources, which are commonly encountered in public sector institutions, also significantly affect audit quality. Furthermore, the unique characteristics of the public sector, such as regulatory complexity and public accountability demands, influence both the conceptualization and measurement of audit quality. This study is expected to provide a theoretical foundation for the development of a conceptual framework for public sector audit quality and to contribute to improving audit practices, governance, and accountability in public financial management.